Ідеографічне систематизування українського неолексикону (за матеріалами нових тлумачних словників) - Сніжко, Н. (Лексикографічний бюлетень, 2018)
У статті представлено методику ідеографічного опису нової української лексики, засвідченої сучасною тлумачною лексикографією. Подаємо ієрархічно структуровані ідеографічні групи новотворів Олеся Гончара, які формуємо у процесі укладання двох нових тлумачних словників – «Словника мови творчої особистості» та «Неолексикона Олеся Гончара ». Вони увиразнюють ідіостиль письменника, виявляють динаміку українського лексикону, мовної та концептуальної картин світу. The article presents a methodology of integrated lexicographic modeling of ideographic groups of the new Ukrainian vocabulary. The basis of modeling is the modern academic explanatory dictionaries, which present new lexical and artistic means of the language of Ukrainian writers and publicists of the XX–XXI centuries. In the process of compiling new explanatory dictionaries, we allocate hierarchically ordered ideographic groups of words and analyze the system of dictionary identifiers of meaning, which are important for the formation of the conceptual scheme of the writer’s worldview. The new explanatory “Dictionary of the Creative Person Language”, which is being worked on by lexicographers of the Institute of Ukrainian Language of the NAS of Ukraine, expresses the leading conceptual dominants and linguistics of each writer and reproduces a common Ukrainian worldview. According to the neo-lexicon of Oles Honchar (words not yet certified by explanatory dictionaries) we build the basis of the conceptual sphere of the new Ukrainian worldview of the second half of the twentieth century. We compare it with the conceptual dominants of the “Dictionary of the Ukrainian Language” (1970–1980), and build the dynamics of linguistic and social development. New explanatory dictionaries fills the gap in the lexical system of language associated with the reproduction of the era of totalitarianism. The ideographic groups of the new vocabulary of Oles Honchar testify to the active creation of appreciative names of people and public relations, the introduction to active use of composites and juxtaposites, complex names of people with expressive connotative semantics. Oles Honchar’s Neolexicon attests to different conceptual groups of vocabulary, reveals a constructive way of writing a writer, and expresses his significant contribution to the development of the national artistic-figurative system. Thus, ideographic systematization of new and actualized vocabulary based on new explanatory dictionaries is an effective way of integral study of the dynamics of language, the role of creative personalities in enriching its expressive and pictorial means, is the basis for perspective modeling of linguistic and conceptual pictures of the world.